Depression and memory function – evidence from cross-lagged panel models with unit fixed effects in ELSA and HRS. Issue 8 (11th June 2022) - Jindra, Christoph; Li, Chenlu; Tsang, Ruby S. M.; Bauermeister, Sarah; Gallacher, John
Abstract: Background: Individuals with depression are often found to perform worse on cognitive tests and to have an increased risk of dementia. The causes and the direction of these associations are however not well understood. We looked at two specific hypotheses, the aetiological risk factor hypothesis and the reverse causality hypothesis. Method: We analysed observational data from two cohorts, English Longitudinal Study of Ageing (ELSA) and Health and Retirement Study (HRS), using cross-lagged panel models with unit fixed effects. Each model was run once with depression and repeated with cognition as the dependent variable and the other variable as the main explanatory variable. All models were estimated separately for contemporaneous effects and lagged effects up to 8 years in the past. We contrasted the results with models making the random effects assumption. Results: Evidence from the fixed effects models is mixed. We find no evidence for the reverse causality hypothesis in ELSA and HRS. While there is no evidence for the aetiological risk factors hypothesis in ELSA, results from HRS indicate some effects. Conclusion: Our findings suggest that current levels of cognitive function do not influence future levels of depression. Results in HRS provide some evidence that current levels of depressive symptoms influence future cognition.